Lexical Gaps In Adjective Comparison Between English And Uzbek (Texas Journal of Philology, Culture and History, 2025)
This paper explores lexical gaps in adjective comparison between English and Uzbek, focusing on the morphosyntactic, semantic, and cultural dimensions that contribute to asymmetries in expressing comparative and superlative degrees. Through contrastive analysis, the study identifies adjectives present in one language but lacking direct equivalents in the other, and examines the implications for translation, second language acquisition, and cross-cultural communication.